Análise do processo de formação e implantação da Cooperativa Central Oeste Catarinense Ltda., na região oeste de Santa Catarina: 1969 - 1973 - Lima, Joseane de (2018)
The present study analyzes the process of formation and implantation of Cooperativa Central Oeste Catarinense Ltda.: Aurora, between 1969 and 1973 in the city of Chapecó, since there were several strategic articulations either by the owners of the local means of production, or by the public representatives of the State, which made it difficult to implement Cooperativa Central Oeste Catarinense Ltda., in the city of Chapecó, therefore, the formation of the Cooperative occurred in 1969, however, its implementation in the municipality began to be effective only in 1972, through the purchase of the Marafon Frigorific also called INCOMASA - Indústria e Comércio Marafon SA, however , the activities of the Cooperative were officialized on October 1973. Therefore, it is proposed to analyze and understand the role of public and private networks, in some make the implementation of Cooperativa Central Oeste Catarinense Ltda., difficult, in this historical-geographic space.